PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 LINGGO SARI BAGANTI - Hidayat, Wirnu - (Pendidikan Matematika, 2014)
This research is motivated by lack of studentâs understanding of matematicalconcepts. The study aims is to determine the understanding of mathematicalconcepts by implementing cooperative learning model Two Stay Two Stray betterthan an understanding of mathematical concepts with conventional learning classVII SMPN 1 Linggo Sari Baganti. Kind of this research is experimental research,with research plan is Randomized to Subject. Population of this research isstudent`s at grade VII SMPN 1 Linggo Sari Baganti. The instrumentation of thisresearch is understanding test of mathematical concepts. Technique of dataanalysis is used in this research is t-test one side by using software MINITAB.Based on the result of t-test is P-value = 0,023, it means lower than ß = 0,05,therefore hipotesis is accepted. We can conclude that student`s understanding ofmathematical concepts is treated by using Two Stay Two Stray better thanstudent`s understanding of mathematical concepts is treated by usingconvensional learning at grade VII SMPN 1 Linggo Sari Baganti.